2020
DOI: 10.53986/ibjm.2020.0018
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of healthcare delivery in the context of COVID-19 pandemic in Sub-Saharan Africa

Abstract: Introduction: Public health security is concerned with infection prevention and control worldwide. These measures are the concern of all and sundry to ensure prevention of any outbreaks of diseases that has epidemic potential. Africa may be uniquely positioned to have the most severe and under-detected outcomes related to COVID-19 infection. This article seeks to highlight such challenges of healthcare delivery systems in the context of the COVID-19 pandemic in sub-Saharan Africa. The communique also suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…The inadequate PPEs and increased work demand has been reported in other countries [ 27 , 28 ]. COVID-19 brought unforetold challenges to healthcare delivery with increasing admissions and a corresponding need to utilize more consumables [ 29 ]. Logistic inadequacy became pronounced in the peak of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The inadequate PPEs and increased work demand has been reported in other countries [ 27 , 28 ]. COVID-19 brought unforetold challenges to healthcare delivery with increasing admissions and a corresponding need to utilize more consumables [ 29 ]. Logistic inadequacy became pronounced in the peak of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…With secondary prevention focusing on early detection of hearing loss, procedures adopted to detect and halt the development of hearing loss before it presents clinically and progresses to levels that lead to adverse outcomes for the individual affected also require contextual awareness and contextual responsiveness (AFMC 2013; WHO 2020). The measures that allow for earlier diagnosis and treatment of hearing loss require political will and therefore mandating by the government -a requirement that requires buy-in by the end-user (the population receiving the service) (Alegbeleye & Mohammed 2020;). If the preventive audiology service delivery does not take careful cognisance of patients' language and culture, challenges with advocacy might arise.…”
Section: Preventive Audiologymentioning
confidence: 99%
“…Additionally, a report from an Iranian hospital revealed that the hospital’s revenue declined by 9%, its costs increased by 70% and the hospital’s balance was reported to be −$607,143 [ 20 ]. Furthermore, African economies were reduced by about 1.4% in gross domestic product (GDP) and faced a contraction of up to 7.8% due to the pandemic, which reduced the capacity of governments to extend the public services necessary to respond to the crisis [ 9 , 21 ]. Furthermore, poor healthcare systems, lack of skilled healthcare professionals, low awareness of disease control and prevention, scarce intensive care units (ICUs) and mechanical ventilators and a high prevalence of underlying diseases were challenges in controlling and preventing the pandemic in low- and middle-income countries, including Ethiopia [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%